Efficient operation of a room-temperature Fe2+:ZnSe laser pumped by a passively Q-switched Er:YAG laser. (October 2017) - Velikanov, S.D.; Gavrishchuk, E.M.; Zakharov, N.G.; Kozlovsky, V.I.; Korostelin, Yu.V.; Lazarenko, V.I.; Maneshkin, A.A.; Podmar'kov, Yu.P.; Saltykov, E.V.; Skasyrsky, Ya.K.; Frolov, M.P.; Tsykin, V.S.; et al.
Abstract: Efficient generation of a train of laser pulses is obtained at room temperature in a Fe 2+ : ZnSe polycrystal pumped by a passively Q -switched Er:YAG laser. The Fe 2+ :ZnSe laser energy reaches 130 mJ at a slope efficiency with respect to the absorbed pump power of 47%. The average pulse repetition rate in the train is ∼100 kHz.